Augmented Reality (AR) as Interactive Education in Islamic Education to Improve Religious Understanding - Fauziah, Arinal Haq (Proceeding of International Conference on Islamic Education (ICIED); Vol 9 No 1 (2024): Proceeding of International Conference on Islamic Education (ICIED)DO - 10.18860/icied.v9i1.3124, 2024)
Islamic education faces the challenge of using traditional methods that are less relevant in the digital era. Augmented reality (AR) technology offers a solution by presenting interactive learning that can increase student engagement, digital literacy and critical thinking. AR provides real visualisation that facilitates students' understanding of religious concepts more deeply. This research uses the phenomenological method of several Islamic educational institutions that have implemented AR. The study will evaluate the effectiveness of AR in complementing or replacing traditional teaching methods as well as its impact on student understanding. The expected result is that AR can improve the quality of religious learning, help students understand religious teachings better, and minimise the spread of misinformation.